2021
DOI: 10.1007/s13300-021-01188-7
|View full text |Cite
|
Sign up to set email alerts
|

Are There Different Viewpoints About the Management of Type 2 Diabetes Mellitus and Comorbidities? A Multidisciplinary Spanish Qualitative Research

Abstract: Introduction:The aim of this study was to explore the vision of a large multidisciplinary group of physicians treating type 2 diabetes mellitus (T2DM) in Spain, with a special focus on controversial management aspects. The perceptions of primary care (PC) physicians and hospital care (HC) specialists were compared. Methods: This was a mixed survey that included Delphi-like statements and opinion, attitude and behaviour (OAB) questions. The Delphi-like statements were assessed on the basis of the degree of agre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
0
1
0
2
Order By: Relevance
“…In addition, two studies demonstrated the benefits of the Mediterranean diet for diabetic patients [56,63]. Another point of interest is the patient-doctor relationship, and accordingly, a qualitative study by a group of doctors in Spain demonstrated the importance of early screening in patients with T2DM, in tandem with good practices, disease control and dietary habits [60]. Conversely, poor diabetes control and poor healthy lifestyle practices lead to complications of the disease [54,63].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, two studies demonstrated the benefits of the Mediterranean diet for diabetic patients [56,63]. Another point of interest is the patient-doctor relationship, and accordingly, a qualitative study by a group of doctors in Spain demonstrated the importance of early screening in patients with T2DM, in tandem with good practices, disease control and dietary habits [60]. Conversely, poor diabetes control and poor healthy lifestyle practices lead to complications of the disease [54,63].…”
Section: Discussionmentioning
confidence: 99%
“…Another qualitative study of a multidisciplinary group of physicians in Spain expressed the importance of early screening in patients with type 2 DM, healthy lifestyle interventions, glycosylated blood glucose testing and glycaemic control as key strategies for reducing the prevalence of the disease [60].…”
Section: Preventive Measures Applied For the Control Of The Diseasementioning
confidence: 99%
“…Lleva razón la OMS con esta estrategia porque los profesionales de medicina de familia estamos en una posición privilegiada para realizar un abordaje holístico y lineal de nuestros pacientes gracias a la accesibilidad, proximidad y continuidad asistencial inherente al trabajo en atención primaria. Este abordaje es un continuum que acompaña al paciente en sus diferentes momentos vitales 2 . Como en muchas otras enfermedades, la Abordaje holístico: La clave en el paciente con diabetes mellitus la glucemia, la tensión arterial y los lípidos en pacientes con DM2 evolucionada aumentó la esperanza de vida, se redujeron los eventos cardiovasculares (EvCV) y los eventos microvasculares en torno al 50 % en el grupo intervención y se constató una ganancia de vida media de 7,9 años, debido fundamentalmente a la reducción o demora en la aparición de los EvCV 5 .…”
Section: La Diabetes Mellitus Desde La Perspectiva De La Atención Pri...unclassified
“…Palabras clave: prevención, protección, iSGLT-2, dapagliflozina. evolución natural de la diabetes mellitus (DM) se desarrolla en diferentes fases, desde la exposición al factor desencadenante, la instauración de la enfermedad hasta las fases más avanzadas donde aparecen las complicaciones 2 .…”
Section: Introductionunclassified
“…Related studies have pointed out that various complications are caused by improper blood glucose control, including retinal-related complications (accounting for 72.6% of the patients), peripheral neuropathy (68.2%), and foot ulcers (12.7%) [ 7 ]. Related research has found that more chronic diseases of diabetic patients and longer time of the illness affect their self-management status [ 7 , 8 ], while their suffering from comorbidities is twice as higher as non-diabetic patients [ 9 ].…”
Section: Introductionmentioning
confidence: 99%